Taurine Supplementation Alleviates Blood Pressure via Gut–Brain Communication in Spontaneously Hypertensive Rats - Qing Su; Xiong-Feng Pan; Hong-Bao Li; Ling-Xiao Xiong; Juan Bai; Xiao-Min Wang; Xiao-Ying Qu; Ning-Rui Zhang; Guo-Quan Zou; Yang Shen; Lu Li; Li-Li Huang; et al. (Biomedicines)
Objects: Taurine exhibits protective effects in the context of cardiovascular pathophysiology. A range of evidence suggests that hypertension activates inflammatory responses and oxidative stress in the paraventricular nucleus (PVN), elevating the arterial tone and sympathetic activity, while it induces gut–brain axis dysfunction in the context of hypertension. However, the mechanism underlying taurine’s anti-hypertensive effects via the gut–brain axis remains unclear. Method: Male spontaneously hypertensive rats (SHRs) were administered 3% taurine in their drinking water for eight weeks, with their arterial pressure measured weekly. Molecular techniques were employed to investigate taurine’s effects on the hypertensive gut and PVN. Additionally, 16S rRNA gene sequencing was used to analyze the gut microbiota composition, and untargeted metabolomics was applied to assess the fecal metabolites following taurine supplementation. Results: Taurine supplementation not only reduced the blood pressure, sympathetic activity, and inflammatory and oxidative stress in the PVN but also improved the cardiac pathology and microbiota composition while alleviating gut inflammation in hypertensive rats. The untargeted metabolite analysis indicated that the primary effect of the taurine intervention in SHRs was exerted on tryptophan metabolism. The levels of serum metabolites such as kynurenine, L-tryptophan, serotonin (5-HT), and 5-hydroxyindole-3-acetic acid (5-HIAA) were altered in hypertensive rats following taurine treatment. Conclusions: Taurine supplementation restored the microbiota balance, strengthened the mucosal barrier, reduced intestinal inflammation, and stimulated tryptophan metabolism. The metabolites derived from the gut microbiota likely crossed the brain barrier and reached the paraventricular nucleus, thereby reducing the inflammatory responses and oxidative stress in the PVN via gut–brain communication, leading to decreased sympathetic nerve activity and blood pressure in the studied hypertensive rats.